Radikalisme sebagai Blocking Factor bagi Perkembangan Peradaban Islam Modern - Syafaq, Hammis (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This article highlights the evolution of Islamic civilization starting from its glory during the classical period until its collapse in modern times. This article also discusses radicalism as a part of inhibiting factors of the development of Islamic civilization in the modern era. Radicalism is a model of understanding which tends to be destructive. This model of understanding has been a fertile ground of the emergence of rigid and normative theological understanding. Hostile attitude of the followers of radicalism often trap them into combat actions of others, even to the extent of murder, especially to the Western people. Such radical attitude has been also manifested in the form of destruction of public facilities. This destructive action has led to the devastation of civilization, which has been built by a nation. The conditions of a number of Arab-Muslim countries, which have not been free from prolonged internal warfare, prove that radicalism is an obvious blocking factor in the development of Islamic civilization in the modern era. Keywords: radicalism, blocking factor, Islamic civilization.